Relationship between Achievement Goal Orientation, Fear of Failure and Academic Performance - Roxana-Elena Leonte (Babes-Bolyai University, 2023)
There is considerable empirical support for the study of factors that positively or negatively influence academic performance, including achievement goal orientation and fear of failure. According to research, fear of failure can, in some situations, threaten students' academic performance by affecting their engagement in learning activities. If remedial action is not taken to reduce it, this can affect students academic future. At the same time, earlier research has indicated that fear of failure influences thenature of achievement goals that students pursue. Nevertheless, there is a scarcity of studies that have explored the connection interplay between learning goal orientation, the fear of failure, and academic achievement. Based on data from 120 university students, we conducted correlational analyses to test the relationships between achievement goal orientation, fear of failure and academic performance. The findings showed significant correlations between fear of failure and mastery-avoidance goal, as well as between students' academic performance. Pedagogical implications and future research directions were discussed.